2010
DOI: 10.1345/aph.1m489
|View full text |Cite
|
Sign up to set email alerts
|

Atazanavir-Associated Choledocholithiasis Leading to Acute Hepatitis in an HIV-infected Adult

Abstract: Atazanavir should be considered a possible contributor in the development of cholelithiasis or choledocholithiasis, and people with HIV should receive adequate counseling in the recognition of symptoms associated with gallstones. The exact incidence and mechanism still need to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
(8 reference statements)
1
4
1
Order By: Relevance
“…An increase in ALP within the normal range, has been detected in both groups and this is in accordance with previous reports on atazanavir containing regimens [30]. In addition, previous studies have shown that abacavir use in combination with atazanavir-r may result in abnormal fasting lipid profile as was the case with ART_B group [31][32][33].…”
Section: Discussionsupporting
confidence: 91%
“…An increase in ALP within the normal range, has been detected in both groups and this is in accordance with previous reports on atazanavir containing regimens [30]. In addition, previous studies have shown that abacavir use in combination with atazanavir-r may result in abnormal fasting lipid profile as was the case with ART_B group [31][32][33].…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports suggested the association between ATV/r use and cholelithiasis [4][6]. However, the association was not demonstrated in this cohort study of 1,242 patients.…”
Section: Discussioncontrasting
confidence: 91%
“…This incidence is 10 times lower than that of ATV/r-associated renal stones reported in our previous study [3]. In fact, only 16 cases with ATV/r-induced cholelithiasis have been reported to date [4][6], compared with substantial number of ATV/r-associated renal stone reported by several groups [3], [12][16]. Thus, the potential risk of cholelithiasis in patients on PIs seems low compared to urolithiasis and may not be a major factor in the selection of ART.…”
Section: Discussionmentioning
confidence: 56%
“…It is well known that ATV/r is associated with renal lithiasis and there have been reports of ATV-associated choledocholithiasis [2][3][4]. We can postulate that our patients may have had semicircular canal lithiasis causing similar symptoms, though the short duration between onset and starting the drug and the complete resolution of symptoms after stopping the drug make this mechanism less likely.…”
Section: Discussionmentioning
confidence: 69%
“…In this case the patient had a 3-year history of ATV, 3TC and TDF use and was admitted to hospital for objective vertigo, nausea and sweating triggered by postural changes. He was diagnosed as having lithiasis of his posterior semicircular canal, possibly related to his ATV use [1].It is well known that ATV/r is associated with renal lithiasis and there have been reports of ATV-associated choledocholithiasis [2][3][4]. We can postulate that our patients may have had semicircular canal lithiasis causing similar symptoms, though the short duration between onset and starting the drug and the complete resolution of symptoms after stopping the drug make this mechanism less likely.…”
mentioning
confidence: 92%